A Nation for All : Race, Inequality, and Politics in Twentieth-Century Cuba - Fuente, Alejandro de la, 1963- (Book collections on Project MUSE., 2001)
Tracing the formation of nationalist ideologies, government policies, and different forms of social and political mobilization in twentieth-century Cuba, Fuente explores the opportunities and limitations that Afro-Cubans experienced in such areas as job access, education, and political representation.